Islamic Principles in Mental Medicine - Abdillah, Yahya Nur; Algristian, Hafid; Azizah, Nur (Jurnal Medis Islam Internasional, 2022)
Background: The religion of monotheism is the religious instinct of every human being as a creature created by Allah SWT. One of the mental health therapies is religion. Islam is the prevailing religion in almost 56 nations around the globe and has more than 1.2 billion adherents. Islam speaks to an all-encompassing way of life and agrees with its supporters' expansive extent. The development of psychiatry in Islam has several reviews. Many Islamic figures contributed to treating mental illness long before Western figures discovered it. At the time of the Prophet Muhammad SAW, there was also a treatment for mental illness based on the Qur'an. This article will mention several forms of worship as psychotherapy. Objective: The purpose of this article is to determine the role of the Islamic Principle in Mental Medicine. Methods: The design of this research is a literature review or library review, which is a systematic, direct, and reproducible research method by identifying, evaluating, and synthesizing published research. Result: Islamic principles in mental medicine consist of tawheed religion as mental therapy, worship as human psychotherapy, islamic psychotherapy to help psychiatric treatment and healing process.  Conclusion: There are five ways of prayer that a Muslim can do as psychological therapy, namely: Saalat, Dhzikr, reading the Qur'an, Shaum, and Hajj. In an Islamic intellectual, there is a discipline of Islamic Psychotherapy that is an integral part of Islamic Psychotherapy; Istinbath, Iqtibas, and Istiqro.